1. The problem statement, all variables and given/known data Use implicit differentiation to find y' given y/(x-y) = x^2+1. 2. Relevant equations 3. The attempt at a solution Hi, I'm doing an online course for Calculus 12, and I have been struggling with Implicit Differentiation. I am hoping someone could maybe help me. Thanks. I'm not positive I'm doing this right, but maybe someone can point me in the right direction. This is what I have so far y/(x-y) = x^2+1 y=(x^2+1)(x-y) y' = (2x)(x-y)+(x^2+1)(1-y') y' = 2x^2-2xy+x^2-x^2y'+1-y' This is where I get stuck and am not sure if I'm making a mistake or know what to do next. Any help would be appreciated, thank you.